2022
DOI: 10.1177/1420326x211061685
|View full text |Cite
|
Sign up to set email alerts
|

Louver and window position effect on cross-ventilation in a generic isolated building: A CFD approach

Abstract: Natural ventilation has been used to increase indoor air quality, remove pollutants, and remove heat absorbed in the building structure. Some architectural features such as wind-catcher systems are used to induce airflow into buildings, and openings equipped with louvers are employed to reduce solar daylight while allowing natural ventilation. Earlier studies on ventilated louvers and wind-catchers have shown the impact of the louvers’ opening positions and slat angles. However, their combination with each oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…The computational fluid dynamics (CFD) technique has recently become more familiar in forecasting natural ventilation performance as computing capability has advanced (Cook et al, 2003;Cook & Lomas, 1998;Liu et al, 2009Liu et al, , 2015Liu et al, , 2018Nielsen, 2015;Qi & Wei, 2020;Yazarlou & Barzkar, 2022;Zhai, 2006;Zhang et al, 2022). Wind-driven CFD tests have demonstrated that the passive technique can meet thermal comfort while enhancing air velocity by reducing indoor temperatures and energy consumption (Elshafei et al, 2017;Hong et al, 2017;Raji et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The computational fluid dynamics (CFD) technique has recently become more familiar in forecasting natural ventilation performance as computing capability has advanced (Cook et al, 2003;Cook & Lomas, 1998;Liu et al, 2009Liu et al, , 2015Liu et al, , 2018Nielsen, 2015;Qi & Wei, 2020;Yazarlou & Barzkar, 2022;Zhai, 2006;Zhang et al, 2022). Wind-driven CFD tests have demonstrated that the passive technique can meet thermal comfort while enhancing air velocity by reducing indoor temperatures and energy consumption (Elshafei et al, 2017;Hong et al, 2017;Raji et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…1 Natural ventilation is of great significance in preventing the spread of aerosol-transmitted diseases indoors. [2][3][4][5] A survey of window-opening habits of Chinese residents revealed that 86.8% of the residents chose single-sided ventilation in northern China. 6 Therefore, single-sided natural ventilation is an important ventilation mode for residential buildings, 7,8 and it can create a healthy and comfortable indoor environment.…”
Section: Introductionmentioning
confidence: 99%